Networks of Power : Political Relations in the Late Postclassic Naco Valley (2011)
Networks of Power reconstructs the course of political history in the poorly documented Naco Valley from the fourteenth through early sixteenth centuries. Describing the material and behavioral patterns pertaining to the Late Postclassic period using components of three settlements in the Naco Valley of northwestern Honduras, the book focuses on how contests for power shaped political structures. Power-seeking individuals, including but not restricted to ruling elites, depended on networks of allies to support their political objectives. Ongoing and partially successful competitions waged within networks led to the incorporation of exotic ideas and imported items into the daily practices of all Naco Valley occupants. The result was a fragile hierarchical structure forever vulnerable to the initiatives of agents operating on local and distant stages.